Suppression of Collisionless Magnetic Reconnection in the High Ion β, Strong Guide Field Limit - Carlos A. Giai; Colby C. Haggerty; Michael A. Shay; Paul A. Cassak; Zachary K. Davis (The Astrophysical Journal)
In magnetic reconnection, the ion bulk outflow speed and ion heating have been shown to be set by the available reconnecting magnetic energy, i.e., the energy stored in the reconnecting magnetic field ( B _r ). However, recent simulations, observations, and theoretical works have shown that the released magnetic energy is inhibited by upstream ion plasma beta β _i —the relative ion thermal pressure normalized to magnetic pressure based on the reconnecting field—for antiparallel magnetic field configurations. Using kinetic theory and hybrid particle-in-cell simulations, we investigate the effects of β _i on guide field reconnection. While previous works have suggested that guide field reconnection is uninfluenced by β _i , we demonstrate that the reconnection process is modified and the outflow is reduced for sufficiently large ${\beta }_{i}\gt ({B}_{r}^{2}+{B}_{g}^{2})/{B}_{r}^{2}$ . We develop a theoretical framework that shows that this reduction is consistent with an enhanced exhaust pressure gradient, which reduces the outflow speed as ${v}_{\mathrm{out}}\propto 1/\sqrt{{\beta }_{i}}$ . These results apply to systems in which guide field reconnection is embedded in hot plasmas, such as reconnection at the boundary of eddies in fully developed turbulence like the solar wind or the magnetosheath as well as downstream of shocks such as the heliosheath or the mergers of galaxy clusters.